High Prevalence of Multidrug-Resistant Clostridioides difficile Following Extensive Use of Antimicrobials in Hospitalized Patients in Kenya - Mutai, Winnie C.; Mureithi, Marianne W.; Anzala, Omu; Revathi, Gunturu; Kullin, Brian; Burugu, Magdaline; Kyany’a, Cecilia; Odoyo, Erick; Otieno, Peter; Musila, Lillian (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction Clostridioides difficile is a neglected pathogen in many African countries as it is generally not regarded as one of the major contributors toward the diarrheal disease burden in the continent. However, several studies have suggested that C. difficile infection (CDI) may be underreported in many African settings. The aim of this study was to determine the prevalence of CDI in hospitalized patients, evaluate antimicrobial exposure, and detect toxin and antimicrobial resistance profiles of the isolated C. difficile strains. Methods In this cross-sectional study, 333 hospitalized patients with hospital-onset diarrhoea were selected. The stool samples were collected and cultured on cycloserine-cefoxitin egg yolk agar (CCEY). Isolates were presumptively identified by phenotypic characteristics and Gram stain and confirmed by singleplex real-time PCR (qPCR) assays detecting the species-specific tpi gene, toxin A (tcdA) gene, toxin B (tcdB) gene, and the binary toxin (cdtA/cdtB) genes. Confirmed C. difficile isolates were tested against a panel of eight antimicrobials (vancomycin, metronidazole, rifampicin, ciprofloxacin, tetracycline, clindamycin, erythromycin, and ceftriaxone) using E-test strips. Results C. difficile was detected in 57 (25%) of diarrheal patients over the age of two, 56 (98.2%) of whom received antimicrobials before the diarrheal episode. Amongst the 71 confirmed isolates, 69 (97.1%) harbored at least one toxin gene. More than half of the toxigenic isolates harbored a truncated tcdA gene. All isolates were sensitive to vancomycin, while three isolates (2.1%) were resistant to metronidazole (MIC >32 mg/L). High levels of resistance were observed to rifampicin (65/71, 91.5%), erythromycin (63/71, 88.7%), ciprofloxacin (59/71, 83.1%), clindamycin (57/71, 80.3%), and ceftriaxone (36/71, 50.7.8%). Among the resistant isolates, 61 (85.9%) were multidrug-resistant. Conclusion Multidrug-resistant C. difficile strains were a significant cause of healthcare facility-onset C. difficile infections in patients with prior antimicrobial exposure in this Kenyan hospital.